ASPEK LINGKUNGAN DAN PRODUKTIVITAS AYAM BROILER PADA SISTEM TRANSPORTASI TERTUTUP DAN KONVENSIONAL - Kiswanto S. Heri; Alvin Fatikhunnada; Mohamad Solahudin (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2014)
Population of broiler chicken increase continuously every year. This situation indicated broiler farm in Indonesia has been transformed as a poultry industry. Broiler farm concentrated in one place far from human to anticipate the potency of air pollution. Transportations are used to mobilize broiler from farm to slaughter house or market. The transportation should consider the condition of broiler and environment to minimize the air pollution and negative effect in broiler performance. This research was aimed to evaluate effect of covered and conventional transportation system on environmental aspect and broiler performance. Sixty broilers was used in this research and divided into two treatments. Data was analyzed by t-Test with α 0.05. The result indicated that covered system better to reduce the potency of ammonia pollution than conventional system. Weight loss of broiler transported with covered system significantly lower (P<0.05) than conventional system. There were no mortality both in conventional and covered system. Distribution of temperature in covered system was significantly lower (P<0.05) than conventional system. Covered system, poultry transportation system based on animal welfare aspect showed lower in vocalization than conventional system.Keywords: broiler, ammonia, environment, productivity